Comparison of Chemical and Heating Methods to Enhance Latent Fingerprint Deposits on Thermal Paper. Issue 2 (21st November 2013) - Bond, John W.
Abstract A comparison is made of proprietary methods to develop latent fingerprint deposits on the inked side of thermal paper using either chemical treatment (Thermanin) or the application of heat to the paper (Hot Print System). Results with a trial of five donors show that the application of heat produces statistically significantly more fingerprint ridge detail than the chemical treatment for both fingerprint deposits aged up to 4 weeks and for a nine sequence depletion series. Subjecting the thermal paper to heat treatment with the Hot Print System did not inhibit subsequent ninhydrin chemical development of fingerprint deposits on the noninked side of the paper. A further benefit of the application of heat is the rapid development of fingerprint deposits (less than a minute) compared with up to 12 h for the Thermanin chemical treatment.